Introduction: constellations and contestations of mobility and space in South Asian ritual journeys - Bergmann, Christoph; Schaflechner, Jürgen (Ritual journeys in South Asia, 2019)
We feel that conceptual developments within studies of spatiality and mobility have not yet been sufficiently applied to research done on